The prognostic value of biological markers in paediatric Hodgkin lymphoma. - Farruggia, Piero; Puccio, Giuseppe; Sala, Alessandra; Todesco, Alessandra; Buffardi, Salvatore; Garaventa, Alberto; Bottigliero, Gaetano; Bianchi, Maurizio; Zecca, Marco; Locatelli, Franco; Pession, Andrea; Pillon, Marta; et al. (Eur J Cancer, 2016)
BACKGROUND: Many biological and inflammatory markers have been proposed as having a prognostic value at diagnosis of Hodgkin lymphoma (HL), but very few have been validated in paediatric patients. We explored the significance of these markers in a large population of 769 affected children. PATIENTS AND METHODS: By using the database of patients enrolled in A.I.E.O.P. (Associazione Italiana di Emato-Oncologia Pediatrica) trial LH2004 for paediatric HL, we identified 769 consecutive patients treated with curative intent from 1st June 2004 to 1st April 2014 with ABVD (doxorubicin, bleomycin, vinblastine, and dacarbazine), or hybrid COPP/ABV (cyclophosphamide, vincristine, prednisone, procarbazine, doxorubicin, bleomycin and vinblastine) regimens. RESULTS: On multivariate analysis with categorical forms, the 5-year freedom from progression survival was significantly lower in patients with stage IV or elevated value of platelets, eosinophils and ferritin at diagnosis. Furthermore, stage IV and eosinophils seem to maintain their predictive value independently of interim (after IV cycles of chemotherapy) positron emission tomography. CONCLUSION: Using the combination of four simple markers such as stage IV and elevated levels of platelets, ferritin and eosinophils, it is possible to classify the patients into subgroups with very different outcomes.
Keywords: Adolescent; Age Factors; Antineoplastic Combined Chemotherapy Protocols; Biomarkers, Tumor; Blood Platelets; Child; Child, Preschool; Databases, Factual; Disease Progression; Disease-Free Survival; Eosinophils; Female; Ferritins; Hodgkin Disease; Humans; Infant; Infant, Newborn; Italy; Kaplan-Meier Estimate; Leukocyte Count; Male; Multivariate Analysis; Neoplasm Staging; Platelet Count; Predictive Value of Tests; Proportional Hazards Models; Retrospective Studies; Risk Factors; Time Factors; Treatment Outcome

Autoimmune hematological diseases after allogeneic hematopoietic stem cell transplantation in children: an Italian multicenter experience. - Faraci, Maura; Zecca, Marco; Pillon, Marta; Rovelli, Attilio; Menconi, Maria Cristina; Ripaldi, Mimmo; Fagioli, Franca; Rabusin, Marco; Ziino, Ottavio; Lanino, Edoardo; Locatelli, Franco; Daikeler, Thomas; et al. (Biol Blood Marrow Transplant, 2014)
Autoimmune hematological diseases (AHDs) may occur after allogeneic hematopoietic stem cell transplantation (HSCT), but reports on these complications in large cohorts of pediatric patients are lacking. Between 1998 and 2011, 1574 consecutive children underwent allogeneic HSCT in 9 Italian centers. Thirty-three children (2.1%) developed AHDs: 15 autoimmune hemolytic anemia (45%), 10 immune thrombocytopenia (30%), 5 Evans' syndrome (15%), 2 pure red cell aplasia (6%), and 1 immune neutropenia (3%). The 10-year cumulative incidence of AHDs was 2.5% (95% confidence interval, 1.7 to 3.6). In a multivariate analysis, the use of alternative donor and nonmalignant disease was statistically associated with AHDs. Most patients with AHDs (64%) did not respond to steroids. Sustained complete remission was achieved in 87% of cases with the anti-CD20 monoclonal antibody (rituximab). Four patients (9%) (1 autoimmune hemolytic anemia, 1 Evans' syndrome, 2 immune thrombocytopenia) died at a median of 87 days after AHD diagnosis as a direct or indirect consequence of their disorder. Our data suggest that AHDs are a relatively rare complication occurring after HSCT that usually respond to treatment with rituximab.
Keywords: Child; Child, Preschool; Female; Hematologic Diseases; Hematopoietic Stem Cell Transplantation; Humans; Italy; Male; Remission Induction; Risk Factors; Transplantation Conditioning

Childhood high-risk acute lymphoblastic leukemia in first remission: results after chemotherapy or transplant from the AIEOP ALL 2000 study. - Conter, Valentino; Valsecchi, Maria Grazia; Parasole, Rosanna; Putti, Maria Caterina; Locatelli, Franco; Barisone, Elena; Lo Nigro, Luca; Santoro, Nicola; Aricò, Maurizio; Ziino, Ottavio; Pession, Andrea; Testi, Anna Maria; et al. (Blood, 2014)
The outcome of high-risk (HR) acute lymphoblastic leukemia patients enrolled in the AIEOP-BFM ALL 2000 study in Italy is described. HR criteria were minimal residual disease (MRD) levels ≥10(-3) at day 78 (MRD-HR), no complete remission (CR) at day 33, t(4;11) translocation, and prednisone poor response (PPR). Treatment (2 years) included protocol I, 3 polychemotherapy blocks, delayed intensification (protocol IIx2 or IIIx3), cranial radiotherapy, and maintenance. A total of 312 HR patients had a 5-year event-free survival (EFS) of 58.9% (standard error [SE] = 2.8) and an overall survival of 68.9% (SE = 2.6). In hierarchical order, EFS was 45.9% (4.4) in 132 MRD-HR patients, 41.2% (11.9) in 17 patients with no CR at day 33, 36.4% (14.5) in 11 patients with t(4;11), and 74.0% (3.6) in 152 HR patients only for PPR. No statistically significant difference was found for disease-free survival in patients with very HR features [MRD-HR, no CR at day 33, t(4;11) translocation], given hematopoietic stem cell transplantation (HSCT) (n = 66) or chemotherapy only (n = 88), after adjusting for waiting time to HSCT (5.7 months). Patients at HR only for PPR have a favorable outcome. MRD-HR is associated with poor outcome despite intensive treatment and/or HSCT and may qualify for innovative therapies. The study was registered at www.clinicaltrials.gov as #NCT00613457.
Keywords: Adolescent; Antineoplastic Combined Chemotherapy Protocols; Child; Child, Preschool; Combined Modality Therapy; Female; Hematopoietic Stem Cell Transplantation; Humans; Infant; Male; Neoplasm, Residual; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Radiotherapy; Remission Induction; Treatment Outcome

Allogeneic hematopoietic stem cell transplantation for Philadelphia-positive acute lymphoblastic leukemia in children and adolescents: a retrospective multicenter study of the Italian Association of Pediatric Hematology and Oncology (AIEOP). - Fagioli, Franca; Zecca, Marco; Rognoni, Carla; Lanino, Edoardo; Balduzzi, Adriana; Berger, Massimo; Messina, Chiara; Favre, Claudio; Rabusin, Marco; Lo Nigro, Luca; Masetti, Riccardo; Prete, Arcangelo; et al. (Biol Blood Marrow Transplant, 2012)
Philadelphia-positive acute lymphoblastic leukemia (Ph+ ALL) still represents a major challenge. We report the experience of the Italian Association of Pediatric Hematology and Oncology (AIEOP) with allogeneic hematopoietic stem cell transplantation (HSCT) in children with Ph+ ALL from 1990 to 2008. Sixty-nine patients received HSCT from either a related (37, 54%) or an unrelated (32, 46%) donor. Twenty-five patients (36%) underwent transplantation before 2000 and 44 (64%) after 2000. Twenty-three patients (33%) received Imatinib mesylate treatment before HSCT and seven (10%) after HSCT. After a median follow-up of 56 months, the overall survival (OS) probability was 51% (95% confidence interval [CI], 38-63), the leukemia-free survival (LFS) was 47% (95% CI, 34-59), transplantation-related mortality (TRM) was 17% (95% CI, 10-30), and relapse incidence (RI) was 36% (95% CI, 26-50). Transplantation in first complete remission, female gender, and lower WBC count at diagnosis were associated with a better LFS in both univariate and multivariate analyses. Patients with p210 transcript had a trend for a worse prognosis compared with those who had the p190 transcript. Our series confirms the role of HSCT in the eradication of Ph+ ALL. Early HSCT is recommended once morphologic remission is obtained.
Keywords: Adolescent; Antineoplastic Combined Chemotherapy Protocols; Benzamides; Child; Child, Preschool; Disease-Free Survival; Drug Administration Schedule; Female; Fusion Proteins, bcr-abl; Graft vs Host Disease; Hematopoietic Stem Cell Transplantation; Humans; Infant; Italy; Male; Philadelphia Chromosome; Piperazines; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Pyrimidines; Remission Induction; Retrospective Studies; Secondary Prevention; Transplantation, Homologous; Young Adult

Marriage and parenthood among childhood cancer survivors: a report from the Italian AIEOP Off-Therapy Registry. - Pivetta, Emanuele; Maule, Milena M; Pisani, Paola; Zugna, Daniela; Haupt, Riccardo; Jankovic, Momcilo; Aricò, Maurizio; Casale, Fiorina; Clerico, Anna; Cordero di Montezemolo, Luca; Kiren, Valentina; Locatelli, Franco; et al. (Haematologica, 2011)
BACKGROUND: The aim of this study was to describe the patterns of marriage and parenthood in a cohort of childhood cancer survivors included in the Off-Therapy Registry maintained by the Italian Association of Pediatric Hematology and Oncology. DESIGN AND METHODS: We analyzed a cohort of 6,044 patients diagnosed with cancer between 1960 and 1998, while aged 0 to 14 years and who were 18 years old or older by December 2003. They were followed up through the regional vital statistics registers until death or the end of follow up (October 30, 2006), whichever occurred first, and their marital status and date of birth of their children were recorded. The cumulative probabilities of being married and having a first child were computed by gender and compared by tumor type within the cohort. Marriage and fertility rates (the latter defined as the number of live births per woman-year) were compared with those of the Italian population of the same age, gender, area of residence and calendar period by means of the observed to expected (O/E) ratios. RESULTS: During the follow-up period, 4,633 (77%) subjects had not married. The marriage O/E ratios were 0.56 (95% CI: 0.51-0.61) and 0.70 (95% CI: 0.65-0.76) among men and women, respectively. Overall, 263 men had 367 liveborn children, and 473 women had 697 liveborn children. The female fertility O/E ratio was 0.57 (95% CI: 0.53-0.62) overall, and 1.08 (95% CI: 0.99-1.17) when analyses were restricted to married/cohabiting women CONCLUSIONS: Childhood cancer survivors are less likely to marry and to have children than the general population, confirming the life-long impact of their previous disease on their social behavior and choices. The inclusion of counseling in the strategies of management and long-term surveillance of childhood cancer patients could be beneficial to survivors as they approach adulthood.
Keywords: Adult; Child; Child, Preschool; Cohort Studies; Female; Follow-Up Studies; Hematologic Neoplasms; Humans; Infant; Infant, Newborn; Italy; Male; Marriage; Middle Aged; Parents; Registries; Survivors

First case in Italy of acquired resistance to oseltamivir in an immunocompromised patient with influenza A/H1N1v infection. - Campanini, Giulia; Piralla, Antonio; Rovida, Francesca; Puzelli, Simona; Facchini, Marzia; Locatelli, Franco; Minoli, Lorenzo; Percivalle, Elena; Donatelli, Isabella; Baldanti, Fausto (J Clin Virol, 2010)
A pandemic influenza A/H1N1v strain with the neuraminidase H274Y mutation was detected in nasal secretions of a 2-year-old leukemic patient with influenza-like illness after 18 days of treatment with oseltamivir. At baseline, no drug-resistant virus was found, while 4 days after treatment initiation a mixture of wild-type and mutated virus was detected. After treatment interruption, the wild type influenza virus re-emerged and became prevalent in nasal secretions after a few days, suggesting the lower fitness of the mutated virus strain. The patient slowly improved concurrently with a decrease in virus load, which resulted negative 42 days after diagnosis. No other drug-resistant influenza A/H1N1v virus strains have been detected in Italy (up to the end of November 2009) since the first case of the novel A/H1N1v virus was identified in the country (May 2009).
Keywords: Amino Acid Substitution; Antiviral Agents; Bodily Secretions; Child, Preschool; Drug Resistance, Viral; Female; Humans; Immunocompromised Host; Influenza A Virus, H1N1 Subtype; Influenza, Human; Italy; Molecular Sequence Data; Mutation, Missense; Neuraminidase; Nose; Oseltamivir; RNA, Viral; Sequence Analysis, DNA; Treatment Outcome; Viral Load; Viral Proteins; Withholding Treatment